2018
DOI: 10.1177/0951484818761730
|View full text |Cite
|
Sign up to set email alerts
|

Service quality and perceived customer value in community pharmacies

Abstract: A patient's perception of the service provided by a health care provider is essential for the successful delivery of health care. This study examines the value created by community pharmacies-defined as perceived customer value-in the prescription drug market through varying elements of service quality. We develop a path model that describes the relationship between service elements and perceived customer value. We then analyze the effect of perceived customer value on customer satisfaction and loyalty. We use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 52 publications
2
28
0
1
Order By: Relevance
“…The items are presented in Table 1 and they serve as a formative basis for variables with a proven significant impact on the perceived customer value for community pharmacy services [ 62 ]. The perceived customer value further influences consumer satisfaction and consumer loyalty, with a more salient effect in pharmacy services by comparison with other service-intensive industries [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The items are presented in Table 1 and they serve as a formative basis for variables with a proven significant impact on the perceived customer value for community pharmacy services [ 62 ]. The perceived customer value further influences consumer satisfaction and consumer loyalty, with a more salient effect in pharmacy services by comparison with other service-intensive industries [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Service companies depend on front-line service workers to control and communicate a certain image that consumers/patients will associate with the business and with the service [66]. In community practice, technicians have been referred to by pharmacists as the “face” of the pharmacy [67]. Image control demands that service workers act according to scripts that diverge from their actual preferences and capacities.…”
Section: The Aesthetics Of Services Delivery and Consumptionmentioning
confidence: 99%
“…In Germany, Guhl, Blankart and Stargardt (2019), concluded that the service elements of personal interaction, tangible aspects, store policy and availability have a positive effect on perceived customer value and consultation, while reliability does not predominate. On the other hand, Wahyuni, Nurhayani and Indar (2019), concluded that there is a positive relationship between health services and patient loyalty, with a positive effect on the responsiveness and safety dimensions, while no correlation was found between the quality of service or health services variable in terms of the tangibility dimension in Indonesia.…”
Section: Introductionmentioning
confidence: 99%